The Legal Nature of the Additional Payment of Excise Taxes Calculated Using an Increasing Coefficient, and the Problems of Applying the Calculation Method of Additional Excise Tax in the Conditions of Applying an Increased Coefficient - O. A. Nogina (Теоретическая и прикладная юриспруденция)
This article is devoted to the actual problem of analyzing the signs of an additional payment for excise duties, the obligation to pay which arises in connection with exceeding the maximum volume of sales of excisable goods at the end of the calendar year. The article analyzes the problems of tax regulation calculation of an additional payment by the settlement method when determining the unfounded tax benefit received by the taxpayer.